The Global, Regional and Local Politics of Institutional Responses to COVID-19
XIII, 255 p.
Keywords: The shift from response to recovery is now noticeable as the world moves past the paralyzing effects of the COVID-19 pandemic. This book explores responses to the pandemic by international, regional, and local institutions, multilateral action, and crisis prevention efforts at different levels of governance, with a specific focus on the situation of women and children. The contributions in this volume address novel topics and expand the analysis to the different challenges faced by women and children, linking these to the Sustainable Development Goals, to create a holistic view of the true impact of the pandemic. The focus on international and regional cooperation provides further insights on how management of the COVID-19-induced crisis can be altered and improved. Immediate effects of the pandemic were focused on healthcare, but long-term and knock-on effects spread to different societal sectors and must be analyzed to ensure they will be addressed and, ultimately, resolved. Madeleine O. Hosli is Professor of International Relations at Leiden University, The Netherlands. She is author of The European Union and the United Nations in Global Governance (2022) and co-editor of The Changing Global Order (2020) and The Future of Multilateralism: Global Cooperation and International Organization (2021). Amy Blessing is an initiative coordinator at the Global Counterterrorism Forum (GCTF) Administrative Unit based at T.M.C. Asser Institute, The Hague, and treasurer at Women in International Security Netherlands. She previously worked at Leiden University as a program coordinator and has LLMs from the University of Glasgow and University of Copenhagen. Irini Iacovidou is a project coordinator at Perrett Laver, The Netherlands. She has an MSc from Leiden University in International Relations and Diplomacy. Her current research interestsfocus on multilateralism and international cooperation, particularly the EU’s position vis-à-vis its neighboring states. .